Influence of Gas Pressure on The Generation of Nanobubbles For Enhanced Dissolved Oxygen (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
Nanobubble (NB) technology produces highly stable nano-sized bubbles with wide applications in water treatment, agriculture, and aquaculture. This study analyses the influence of gas pressure on NB formation, bubble size distribution, and dissolved oxygen (DO) levels in water, aiming to understand how pressure affects NB characteristics and oxygen dissolution efficiency. NBs were generated using a cartridge nozzle with pressurised oxygen gas at pressure values of 0.1, 0.2, and 0.3 kPa for 30 minutes. The results show that gas pressure is a key parameter for nanobubble size and distribution. At a pressure of 0.1 kPa, the average size was 170 nm, decreasing to 110 nm at 0.2 kPa and 93 nm at 0.3 kPa with a more homogeneous size distribution. As the NB size decreased, the DO concentration increased. The initial DO value of 2.42 mg/L increased rapidly over the first 5 minutes to 32.40 mg/L and then to 35.34 mg/L after 30 minutes for 0,3 kPa pressure. This trend is similar to NBs produced at another pressure. This study confirms that gas pressure variation is an important parameter in controlling NB formation and increasing DO, thereby supporting the development of efficient aeration technology for various applications.
Keywords: dissolved oxygen (DO); gas pressure; nanobubbles; nanobubble size